PENGARUH KEMAMPUAN PEGAWAI DAN MOTIVASI PEGAWAI TERHADAP KINERJA PEGAWAI DI DINAS LINGKUNGAN HIDUP KABUPATEN PONOROGO - Yulantias, Alfania; Djumiarti, Titik; Yuniningsih, Tri (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
This research is based on the problem of employee performance at the Ponorogo Regency Environmental Service who have not achieved their performance targets. This research aims to determine how much influence Employee Ability and Employee Motivation partially and simultaneously have on Employee Performance at the Ponorogo Regency Environmental Service. This research uses an explanatory quantitative approach. The number of samples was 60 people obtained using the Slovin formula. The sampling technique uses random sampling. The primary data collection method uses a questionnaire. The research results show that the variables Employee Ability and Employee Motivation simultaneously and significantly influence employee performance. Apart from that, Employee Ability and Employee Motivation have a correlation with Employee Performance of 83.7%, while the rest is influenced by other variables not examined in this research. In conclusion, based on the research results, it is stated that Employee Ability and Employee Motivation have a positive and significant effect on Employee Performance at the Ponorogo Regency Environmental Service, however improvements are needed, such as strengthening employee regulations so that they do not arrive late and improving facilities to support employees in carrying out their performance.